METHODS OF IMPLEMENTING SYSTEMATIC ANALYSIS IN TEACHING SPECIALISTS - B.J. Khursanov (Western European Studies, 2023)
The article presents the methods of systematic analysis in the teaching of specialized sciences, the requirements for them, and methods of intensifying the process. The methods of systematic analysis in pedagogical activities have been studied. Conclusions are given on the basis of the scientific-research works carried out in recent years in the field of chemistry.
Keywords: machine creation; document study; activity product study